THE ROLE OF THE COACH IN PLAYER DEVELOPMENT: MODERN TRAINING APPROACHES - Нестеренко, Наталія (SWorldJournal, 2025)
The article examines the contemporary transformation of the coach’s role in sports, driven by technological advancements, new developments in sports science, and evolving interaction models between coaches and athletes. The study analyzes modern trends in